PERANAN SYEIKH ABDUL FATTAH DALAM MENGEMBANGKAN AGAMA ISLAM DI DESA MUMPA KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Sari, Rafina Ria; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of the research is (1) to find out Syeikh Abdul Fattah biography; (2) to find out the efforts that have been clone by Syeikh Abdul Fattah in expanding the islamic religion in Mumpa Village Sub district of Tempuling Indragiri Hilir regency; (3) to find out the obstacies dealt with Syeikh in expanding the islamicrelegion in Mumpa village sub district of Tempuling Indragiri Hilir regency; (4) to find out the influence of islamicrelegion expending which has been done by Syeikh Abdul Fattah towards people condition in Mumpa village Sub district of Tempuling Indragiri Hilir regency. This research uses avalitative research, by historical approach and data collection techtique are documentation, observation, and interview. The respondents of the research are Syeikh Abdul Fattah’s Family and the religious figures. The result of this research areSyeikh Abdul Fattah is a muslimrelegious teacher who expanded islamic teaching in Indragiri Hilir. The role of Syeikh Abdul Fattah for Indragiri Hilir people can be seen from the efforts which have been done by him missionary endeavor and education and also Syeikh Abdul Fattah is a muslimrelegious teacher who expanded islmamic teaching very persistently and never give up.Key Words :The Role, Expanding The Islamic Relegion